Hybrid Laser Technology for Composite Coating and Medical Applications - Jelínek, Miroslav; Kocourek, Tomáš; Písařík, Petr; Mikšovský, Jan; Remsa, Jan; Mihailescu, Ion N.; Kopeček, Jaromír (Penerbit Universiti Sains Malaysia, 2014)
Nano-composite layers were synthesised by pulsed laser deposition (PLD) combined with magnetron sputtering, ion gun modification and RF discharges, and by dual pulsed laser ablation using simultaneously two KrF excimer lasers and two targets. Diamond-like carbon (DLC), Cr-containing diamond-like carbon (Cr-DLC), silver-doped hydroxyapatite (Ag-HA) and silver doped 316L steel and Ti6Al4V were prepared by hybrid laser technologies for potential coating of medical implants. Growing DLC films were modified during the laser deposition (10 J cm–2) by ion bombardment. Energy of argon ions was in the range between 50 eV and 210 eV. Content of sp2 "graphitic" and sp 3 "diamond" bonds, doping, structure, mechanical and biocompatible properties were tested. Deposition arrangements and experiences are presented